Paclitaxel and cisplatin in advanced or recurrent carcinoma of the endometrium: Long-term results of a phase II multicenter study - Dimopoulos, M.A.; Papadimitriou, C.A.; Georgoulias, V.; Moulopoulos, L.A.; Aravantinos, G.; Gika, D.; Karpathios, S.; Stamatelopoulos, S. (Gynecologic Oncology, 2000)
Objectives. Both paclitaxel and cisplatin have moderate activity in patients with metastatic or recurrent carcinoma of the endometrium, and the combination of these two agents has shown activity in a variety of solid tumors. We administered this combination to patients with metastatic or recurrent carcinoma of the endometrium to evaluate its activity and to define its toxicity. Methods. Twenty-four consecutive patients were treated on an outpatient basis with paclitaxel 175 mg/m2 administered intravenously over a 3-h period followed by cisplatin 75 mg/m2 administered intravenously with granulocyte colony-stimulating factor (G-CSF) support. The chemotherapy was repeated every 3 weeks for a maximum of six courses. Results. Sixteen patients (67%; 95% confidence interval, 4584%) achieved an objective response, including seven complete responses and nine partial responses. The median duration of response was 7 months, and the median times to progression and survival for all patients were 8.4 and 17.6 months, respectively. Some degree of neurotoxicity occurred in 44% of patients. Grade 3 or 4 toxicity included granulocytopenia in 22% of patients and peripheral neuropathy in 9%. Conclusion. The combination of paclitaxel with cisplatin with G-CSF support appears active in patients with metastatic or recurrent carcinoma of the endometrium. The significant incidence of neurotoxicity is of concern and alternative methods of administration of the two agents could be evaluated. (C) 2000 Academic Press.
Keywords: Cisplatin; Endometrial cancer; Paclitaxel